2019
DOI: 10.3389/fpls.2019.00131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Chemical Forms of Nitrogen on the Quick and Reversible Inhibition of Soybean Nodule Growth and Nitrogen Fixation Activity

Abstract: It has been reported that supply of nitrate to culture solution rapidly and reversibly inhibits nodule growth and nitrogen fixation activity of soybean. In this study, the effects of ammonium, urea, or glutamine on nodule growth and nitrogen fixation activity are compared with that for nitrate. Soybean plants were cultivated with a nitrogen-free nutrient solution, then 1 mM-N of nitrate, ammonium, glutamine, or urea were supplied from 12 DAP until 17 DAP. Repression of nodule growth and nitrogen fixation activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 42 publications
2
34
0
1
Order By: Relevance
“…This result may have occurred because excessive nitrogen under drought conditions inhibited RuBP carboxylase activity, which led to the decrease in gas exchange parameters and affected the growth of plants ( Nakaji et al., 2002). Alternatively, because R. pseudoacacia functions in biological nitrogen fixation, it can make more effective use of low‐level nitrogen, but excessive nitrogen may inhibit the nitrogen fixation ability of legumes and thus inhibit plant growth ( Yamashita et al., 2019). In addition, under drought conditions, P deficiency obviously weakened the positive effect of the HN treatment on plant height, stem diameter and biomass, which may be because under the condition of soil water deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…This result may have occurred because excessive nitrogen under drought conditions inhibited RuBP carboxylase activity, which led to the decrease in gas exchange parameters and affected the growth of plants ( Nakaji et al., 2002). Alternatively, because R. pseudoacacia functions in biological nitrogen fixation, it can make more effective use of low‐level nitrogen, but excessive nitrogen may inhibit the nitrogen fixation ability of legumes and thus inhibit plant growth ( Yamashita et al., 2019). In addition, under drought conditions, P deficiency obviously weakened the positive effect of the HN treatment on plant height, stem diameter and biomass, which may be because under the condition of soil water deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that low N fertilization (0.7 g N/m 2 ) may have promoted the growth of N-fixing microorganisms in the N-deficient soil. And (2) the influence on N fixation activity was milder for urea than for nitrate and ammonium (Yamashita et al, 2019).…”
Section: Microorganism Community Improved Rocky Soil Qualitymentioning
confidence: 99%
“…Primary roots were separated from the laterals root of each plant when collecting samples and immediately transported to the laboratory in an icebox. They were placed in an oven at 110 • C for 15 min after washing with deionized water, then adjusted to 80 • C to dry until constant weight [45,46], and finally ground into a powder then sifted through a 1 mm sieve.…”
Section: Sample Analysismentioning
confidence: 99%